Local cooking wares from the western Nile Delta, Egypt (1st– 3rd century AD) - Simony, Aude (Rei Cretariae Romanae Fautorum Acta, 2022)
Research conducted since the late 1990s in the western part of the Nile Delta, particularly in the city of Alexandria and its chôra, by the Centre d’Études Alexandrines (CEAlex, CNRS) and the Mission Française des Fouilles de Taposiris Magna-Plinthine (IFAO, University of Paris-Nanterre, HiSoMA, CNRS) as well as on the site of Buto/Tell el-Fara’in, located further south on the eastern side of Rosetta branch of the Nile, by the Mission Française de Bouto (IFAO, University of Paris-Nanterre) since 2001, has produced a remarkable amount of ceramic material from both consumption and production contexts. Based on pottery assemblages found on different, recently excavated sites, this paper aims to present local cooking wares produced during Early Roman times (1st-3rd century AD) on the western side of the Delta. This presentation will lay particular stress on the typology of these Egyptian productions – such as cooking pots and cooking pans – and their relationships with imported types, in order to investigate the influence of these importations on local production and to consider the economic vitality of the Western Delta area.